Great saphenous vein stump thrombosis after harvesting for coronary artery bypass graft surgery. (May 2014) - Labropoulos, N; Bishawi, M; Gasparis, A; Tassiopoulos, A; Gupta, S
Objectives: To determine the rate of superficial venous thrombosis in patients undergoing great saphenous vein (GSV) harvesting for coronary artery bypass surgery (CABG). Methods: Post-CABG patients with suspected lower-extremity thrombosis underwent duplex scanning. Thrombus in the saphenofemoral junction stump was noted, and thrombus extension and associated complications collected. Results: Out of 2335 patients who underwent CABG in five years, 98 patients presented with signs and symptoms of lower-extremity thrombosis. Thrombosis was present in 19 (19.4%) of these patients, 15 of which had a thrombus in the GSV. Five patients had significant signs and symptoms of pulmonary embolism (PE). On objective diagnostic imaging, three of them had a PE. Conclusion: Patients undergoing great saphenous vein harvesting for CABG are at an increased risk of developing superficial vein thrombosis especially at the saphenous stump. Given the increased risk of deep vein thrombosis and PE, further studies investigating this topic are warranted.